حص ىًُ و حطى شَ ظَبو قَطت ب غُ - دراجي, عائشة البتول; زين, نور الهدى; عامر, نسيمة (university of eloued جامعة الوادي, 2022)
ػا لٍاً إئلاً في ػاى الأػ اَه. تذ )POS( في اى ق٘د اىحاضش ، أصثحد قّاط اىثيغ ظّا ؤٍذ دَ اٍْسة ، قذ ذظ شٖ الأػ اَه اى س٘قيح اى رَشام حَ قٗذ ذحذز شٍنلاخ رٍؼذدج ظّشًا لأ مو شيء نٍر ب٘ يذ يًٗا في سعو اى شَظح ألا ين ض اَ سلا حٍ اىثيا اّخ حٍقق [ 1]. حيس ذحراض اى رَاظش إىى طشيقح فؼاىح مٗفؤج ىيرخزي إٗػطاء رّيعح شٍ٘ ق٘ح دٗقيقح في مو ؼٍا يٍح ي يٍ٘ح. إْ ذأذي اىحاظح إىى ذط ي٘ش ظّا قّطح تيغ حٍس للحد من هذا الإشكال ير صَو في تش اّ طٍ سطح نٍرة ، يجري عدد كبير وهائل اىؼ يَياخ اٗى ؼَا لٍاخ اىرعاسيح في قٗد قصيش ظذا تٗطشيقح ظٍْ حَ دقيقح . زإ اىثش اّ طٍ يش وَ اىنصيش اىق ا٘ئ اىري ذساػذ صاحة اى رَعش ػيى إداسج ظ يَغ الأقسا اٗلأ شّطح اىرعاسيح م اَ ي ف٘ش شٍاقثح اى ثَيؼاخ ثٍاششج Nowadays, Point of Sale (POS) has become a huge factor in the business world. Without a proper automated system, backlogs of paperwork may arise and various problems may occur since everything is manually written to a log and data integrity is likely to be unrealized [1]. Where stores need an effective and efficient way to store and give a reliable, efficient and accurate result in every daily transaction. Hence the need to develop an improved point of sale system to reduce this problem, represented by a desktop program, which conducts a huge number of commercial operations and transactions in a very short time and in an organized and accurate manner. This program includes a lot of lists that help the store owner to manage all departments and commercial activities and also provides direct sales control.
مذكرة ليسانس اعلام الي
Keywords: قطة البيع ، المبيعات، برنامج سطح مكتب، العمليات والمعاملات التجارية ،المتجر; points of sale, sales, desktop application, commercial operations and transactions, store